Role of microRNA in Bystander Effect of Astrocyte Proliferation Induced by Simulated Space Radiation - QIN Yuhan1, ZHANG Ziyin1, YAN Liben1, GAO Yanan1, WANG Ailu1, ER Tianyi1, LIU Mengjin1, LI Nuomin1, WANG Qiaojuan2, SUI Li2, , MA Hong1, (Yuanzineng kexue jishu)
Astrocytes, the most common cell type in the central nervous system, are particularly sensitive to ionizing radiation. Beyond affecting astrocyte growth, ionizing radiation also exerts bystander effects on neighboring neural cells, leading to damage within the central nervous system. The space environment is inundated with radiation, including solar particle radiation primarily composed of protons and galactic cosmic rays consisting of high-energy protons, heavy ions, and γ-rays. Space radiation represents one of the most significant health risks faced by astronauts during spaceflight missions. To address this, the γ-rays generated by 60Co and heavy ion radiation produced by 12C6+ were employed in this paper. Human brain astrocytoma cells (U-87 cells) were irradiated at varying gradients of doses to explore the tolerance dose corresponding to an 80% cell survival rate and the semi-lethal dose corresponding to a 50% cell survival rate. Subsequently, tolerance doses (2 Gy of γ-rays and 0.2 Gy of heavy ion radiation) and semi-lethal doses (10 Gy of γ-rays and 2 Gy of heavy ion radiation) were administered to U-87 cells to compare the effects of these two types of radiation on bystander cell proliferation in U-87 cells. The results reveal significant differences in cell survival and bystander cell proliferation between γ-rays and heavy ion radiation at both dose levels. Specifically, γ-rays induce a proliferation-promoting bystander effect in astrocytes, while heavy ion radiation lead to a proliferation-inhibiting bystander effect. This suggests that the cellular response to radiation is not uniform and can vary significantly depending on the type and intensity of the exposure. Three proliferation-related microRNAs, namely miR-24-1-5p, miR-100-5p, and miR-7704, were identified through further investigation using RNA high-throughput sequencing technology and bioinformatics analysis. These microRNAs collectively regulate bystander cell proliferation through distinct mechanisms. Additionally, the effect of different radiation types on the intracellular and extracellular distribution of these three microRNAs was assessed. Notably, γ-rays and heavy ion radiation exhibit differential effects on the expression of these microRNAs at varying doses, corresponding to different mechanisms within the cells. The intricate interplay between these microRNAs and their target genes could be pivotal in mediating the cellular response to radiation-induced stress. The above research results indicate the importance of developing targeted protective strategies to mitigate the adverse effects of space radiation on the health of astronauts, particularly focusing on the central nervous system.